Menganalisis Konflik dan Proses Politik di Indonesia dan Upaya Otoritas Menanganinya - Aditya Nanda Saputra; Mohammad Aditya AB; Surya Sukti (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Conflict in society is a complex social phenomenon and inseparable from the dynamics of human life. This study aims to analyze the factors that trigger conflict in society, the role of government authorities in handling conflict, the forms of horizontal and vertical conflict, and the conflict resolution process from a political perspective. The method used is a qualitative approach with library research, which utilizes various sources of the latest scientific literature as secondary data. The results show that conflict is triggered by various interrelated factors, such as social and economic inequality, differences in identity, political dynamics, weak social integration, and suboptimal law enforcement. The government has a strategic role as a regulator, mediator, and stabilizer in resolving conflict, but its success depends heavily on the quality of governance and the level of public trust. Social conflict is classified into horizontal and vertical conflicts, which have different characteristics but influence each other. Meanwhile, political conflict resolution requires a multidimensional approach through negotiation, public policy, legal instruments, and community participation. Thus, a comprehensive and sustainable approach is needed in managing conflict to maintain social stability and national integration